Signaling Pathways Mediating Bradykinin-Induced Contraction in Murine and Human Detrusor Muscle - Borsodi, Kinga; Balla, Helga; Molnár, Péter József; Lénárt, Ádám; Kenessey, István; Horváth, András; Keszthelyi, Attila; Romics, Miklós; Majoros, Attila; Nyirády, Péter; Offermanns, Stefan; Benyó, Zoltán (Frontiers in Medicine, 2022)
Bradykinin (BK) has been proposed to modulate urinary bladder functions and implicated in the pathophysiology of detrusor overactivity. The present study aims to elucidate the signaling pathways of BK-induced detrusor muscle contraction, with the goal of better understanding the molecular regulation of micturition and identifying potential novel therapeutic targets of its disorders. Experiments have been carried out on bladders isolated from wild-type or genetically modified [smooth muscle-specific knockout (KO): Gαq/11-KO, Gα12/13-KO and constitutive KO: thromboxane prostanoid (TP) receptor-KO, cyclooxygenase-1 (COX-1)-KO] mice and on human bladder samples. Contractions of detrusor strips were measured by myography. BK induced concentration-dependent contractions in both murine and human bladders, which were independent of secondary release of acetylcholine, ATP, or prostanoid mediators. B2 receptor antagonist HOE-140 markedly diminished contractile responses in both species, whereas B1 receptor antagonist R-715 did not alter BK’s effect. Consistently with these findings, pharmacological stimulation of B2 but not B1 receptors resembled the effect of BK. Interestingly, both Gαq/11- and Gα12/13-KO murine bladders showed reduced response to BK, indicating that simultaneous activation of both pathways is required for the contraction. Furthermore, the Rho-kinase (ROCK) inhibitor Y-27632 markedly decreased contractions in both murine and human bladders. Our results indicate that BK evokes contractions in murine and human bladders, acting primarily on B2 receptors. Gαq/11-coupled and Gα12/13-RhoA-ROCK signaling appear to mediate these contractions simultaneously. Inhibition of ROCK enzyme reduces the contractions in both species, identifying this enzyme, together with B2 receptor, as potential targets for treating voiding disorders.